Reception. (October 2020) - Bridges, Emma; Stead, Henry
Abstract : Bloomsbury's Imagines series, edited by Filippo Carlà-Uhink and Martin Lindner, focuses on classical receptions in the visual and performing arts. It has blazed into 2020 with three edited volumes and one monograph. The monograph by Carlà-Uhink is on the reception of classical Greece in theme parks, and the edited volume that has landed on our desk is Classical Antiquity in Video Games . In this attractive volume, clad in the stylish graphics of Alientrap's Apotheon (2015), Christian Rollinger has assembled a vital collection of essays on the underexplored subject. As he emphatically proclaims, 'Video games are everywhere' (xiii) and this book is a lifeline for countless university teachers faced with the task of supervising students enthusiastically writing about the ever-expanding mass of classically inspired games.